2017
DOI: 10.1111/jdv.14074
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG and pulsed dye laser therapy in infantile haemangiomas: a retrospective analysis of 271 treated haemangiomas in 149 children

Abstract: Combined Nd:YAG/PDL therapy is an effective and well-tolerated local treatment option for IH of any classification, in any phase of development and at any age. With regard to the systemic use of propranolol, combined Nd:YAG/PDL therapy seems a safe and promising alternative in many cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 47 publications
(109 reference statements)
1
22
1
11
Order By: Relevance
“…Group A: parallel treatment with propranolol and laser therapy Simultaneous propranolol and laser therapy achieved a strong improvement (IV) of the findings in 10/11 (90.9 %) children. An earlier study in 137 children reported strong improvement in 72.2 % of those IH treated with Nd:YAG/PDL combination therapy [41]. Response rates in propranolol treatment are comparable to those in Nd:YAG/PDL combination therapy [8].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Group A: parallel treatment with propranolol and laser therapy Simultaneous propranolol and laser therapy achieved a strong improvement (IV) of the findings in 10/11 (90.9 %) children. An earlier study in 137 children reported strong improvement in 72.2 % of those IH treated with Nd:YAG/PDL combination therapy [41]. Response rates in propranolol treatment are comparable to those in Nd:YAG/PDL combination therapy [8].…”
Section: Discussionmentioning
confidence: 86%
“…Group B: Propranolol first, followed by laser therapy Recurrent IH after initially successful propranolol treatment occurs in up to 25 % of treated children, and in 10-15 % of these, repeat treatment with propranolol is required [8,[27][28][29]. In contrast, recurrence after initially successful laser therapy is rare (2 % according to our own studies) [41]. In this earlier study, non-response to laser therapy requiring subsequent propranolol treatment was seen in 3.6 % of cases [41].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Dabei wurden (vor Zulassung von Propranolol) 149 Kinder mit insgesamt 271 Hämangiomen lasertherapiert, davon 137 Kinder mit 187 Hämangiomen mit der Neodym:YAG‐Farbstofflaser‐Kombinationstherapie. An diesem Kollektiv wurde gezeigt, dass die Neodym:YAG‐Farbstofflaser‐Kombinationstherapie bei jeder Form infantiler Hämangiome (superfiziell, subkutan, gemischt), in jeder Entwicklungsphase des Hämangioms (Proliferation und Regression) und in jedem Kindesalter effektiv ist .…”
unclassified